How Should Business Training be Priced? A Demand Experiment in Jamaica - Maffioli, Alessandro (World Bank, Washington, DC, 2020)
This note examines how sensitive the demand for business training is to price, and whether charging a higher price causes firm owners to exert more effort in training.